Introduction To Marketplace Management For Citizens - Euis Nurul Bahriyah; Ahmad Sururi Afif; Nuridha Matiin; Mutiara Shifa; Sudjinan Sudjinan (Jurnal Insan Pengabdian Indonesia, 2023)
Online marketplaces are so crowded that it can make it easier for someone to trade in everyday life. By introducing this technology to the public in particular, the residents of Rawa Village RT 02/RW 08 Johar New Jakarta Center. It is expected to make it easier for someone to start an online store business, or to facilitate someone to promote their products, therefore by organizing learning in order to devote to the community to socialize the introduction of online marketplace and also provide training on the use of features that exist in the marketplace that can be used by Residents of Kampung Rawa RT 02/RW 08 Johar New Jakarta Center. It is a community service by us.